2014
DOI: 10.1017/s0030605313000537
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity and bottlenecks in a migratory wildebeestConnochaetes taurinuspopulation

Abstract: Surprisingly little is known about the spatial dimensions of most tropical ungulate migrations, including that of wildebeest Connochaetes taurinus, a species famous for long-distance movements. Using non-invasive photographic identification of 834 adult wildebeest from 8,530 images collected over 4 years we characterize patterns of migratory connectivity throughout the northern TarangireManyara Ecosystem, Tanzania. We document movements between Tarangire and Lake Manyara National Parks and northwards to the sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 35 publications
4
55
0
Order By: Relevance
“…We believe these conflicting results may underscore behavioral differences underlying collar data collected during the northward migration, versus detection data collected throughout the year. Our GPS collar data indicated that animals moved quickly northwards from Manyara Ranch towards the breeding grounds once the 445 rains began, often traveling at night through bottlenecks and across high-traffic roads (Morrison and Bolger 2014). Therefore, the collar data likely reflected wildebeest movements during an active migratory state, when animals were moving through open areas such as grasslands without necessarily stopping frequently to forage.…”
Section: Correlates Of Wildebeest Habitat Selectionmentioning
confidence: 85%
See 4 more Smart Citations
“…We believe these conflicting results may underscore behavioral differences underlying collar data collected during the northward migration, versus detection data collected throughout the year. Our GPS collar data indicated that animals moved quickly northwards from Manyara Ranch towards the breeding grounds once the 445 rains began, often traveling at night through bottlenecks and across high-traffic roads (Morrison and Bolger 2014). Therefore, the collar data likely reflected wildebeest movements during an active migratory state, when animals were moving through open areas such as grasslands without necessarily stopping frequently to forage.…”
Section: Correlates Of Wildebeest Habitat Selectionmentioning
confidence: 85%
“…The TE contains a patchwork of reserves, including two national parks, Lake Manyara and Tarangire, as well as Manyara Ranch Conservancy (Fig. 1) that support high wildlife densities during the dry season, but all migratory routes and wet-season calving grounds lie outside formally protected areas (Morrison and Bolger 2014), and movement corridors in the ecosystem are considered to be at 120 high risk of disappearing within the near future (Caro et al 2009;Morrison and Bolger 2014;Morrison et al 2016). …”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations